Working Capital and Solvency Analysis to Increase Profitability at PT Perusahaan Gas Negara Tbk for the 2019-2023 Period - Safira, Eka; Pane, Sri Gustina; Lubis, Farida Khairani (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this study is to determine and analyze working capital and solvency in increasing the profitability of PT Perusahaan Gas Negara Tbk. The data analysis technique used is descriptive analysis. Data collection techniques were carried out through documentation studies and literature studies. The data used in this study are secondary data obtained from the annual financial statements of PT Perusahaan Gas Negara Tbk listed on the Indonesia Stock Exchange (IDX). Based on the results of the study, it is known that the company's net working capital fluctuated and at the end of the period there was a sharp decline. This decline was caused by a greater increase in current liabilities compared to the increase in current assets. The solvency ratio can be said to be quite good, although a high debt to equity ratio (DER) is not ideal, because a higher DER indicates that the company's funding comes more from debt. However, the decreasing value of the debt to asset ratio (DAR) indicates that the company is able to reduce its dependence on debt.